(untitled) (Perner’s Contacts, 2010)
This article deals with problems of public passenger transport from the transport user point of view. Than there are characterized properties of each mode of transport including of course also public passenger transport. Specifically there are following characteristics mentioned in the article: speed of means of transport, length of stay of means of transport in the stops and stations, waste of time and value of time savings.